1995
DOI: 10.1136/jcp.48.8.749
|View full text |Cite
|
Sign up to set email alerts
|

Histological discrimination of idiopathic inflammatory bowel disease from other types of colitis.

Abstract: We reviewed 246 colonic biopsy specimens. Biopsy specimens were fixed in formaldehyde, embedded in paraffin wax, step-sectioned at 4 jum, and stained with haematoxylin and eosin and periodic acid-Schiff. At least 10 serial sec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 14 publications
3
50
1
1
Order By: Relevance
“…This was in agreement with Cotran, (1999) who recorded that the onset of disease peaks between the ages of 20 -25 years, and women are affected more often than men are. Similar findings were also obtained by Seldenrijk, (1991) and Berre et al, (1995) who found that the mean age for UC was 40 years and 39 years respectively, but the opposite was detected for sex predominance as they found that men were affected more often than women. (17,18,19).…”
Section: B a A B C Dsupporting
confidence: 77%
“…This was in agreement with Cotran, (1999) who recorded that the onset of disease peaks between the ages of 20 -25 years, and women are affected more often than men are. Similar findings were also obtained by Seldenrijk, (1991) and Berre et al, (1995) who found that the mean age for UC was 40 years and 39 years respectively, but the opposite was detected for sex predominance as they found that men were affected more often than women. (17,18,19).…”
Section: B a A B C Dsupporting
confidence: 77%
“…7,16,17 The increase of density in active inflammatory bowel diseases exceeds by two to four folds the aggregate proliferation seen close to inflamed diverticula. Moreover, most of aggregates in Crohn's disease and a substantial part of them in ulcerative colitis is positioned deeply in the submucosa or even transmurally.…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is recommended that rather than individual histomorphological features, combination of these changes need to be considered before giving the diagnosis of UC. 2,23 Atypical presentation in UC is not uncommon. We noted one case with rectal sparing.…”
mentioning
confidence: 99%